2021
DOI: 10.3389/fcvm.2021.728885
|View full text |Cite
|
Sign up to set email alerts
|

Atrial High-Rate Event Incidence and Predictors in Patients With Permanent Pacemaker Implantation

Abstract: Objective: The present study aims to investigate the incidence and predictors of atrial high-rate events (AHREs) in patients with permanent pacemaker implants.Methods: A total of 289 patients who were implanted with a dual-chamber pacemaker due to complete atrioventricular block or symptomatic sick sinus syndrome (SSS) and had no previous history of atrial fibrillation were included in the present study. AHREs are defined as events with an atrial frequency of ≥175 bpm and a duration of ≥5 min. The patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Su et al [25] demonstrated success rate of 97.8% in patients undergoing LBBAP with stable thresholds during a mean follow-up of 18.6 months. Particularly, LBBAP is safe and effective in patients ≥80 years old [26], and as AHREs may increase with aging [27,28], older people may benefit more from LBBAP. Additionally, HBP was associated with a significantly higher risk of complications compared with LBBAP (8.6% vs. 1.3%; P = 0.04), mainly because of more lead-related complications, whereas LBBAP was associated with a risk of complications similar to that of RVP (3.5% vs.…”
Section: Discussionmentioning
confidence: 99%
“…Su et al [25] demonstrated success rate of 97.8% in patients undergoing LBBAP with stable thresholds during a mean follow-up of 18.6 months. Particularly, LBBAP is safe and effective in patients ≥80 years old [26], and as AHREs may increase with aging [27,28], older people may benefit more from LBBAP. Additionally, HBP was associated with a significantly higher risk of complications compared with LBBAP (8.6% vs. 1.3%; P = 0.04), mainly because of more lead-related complications, whereas LBBAP was associated with a risk of complications similar to that of RVP (3.5% vs.…”
Section: Discussionmentioning
confidence: 99%